Growth and characterization of an organic non linear Optical single crystal: BisPicolonium Tartrate. (2019) - Viju, G.; Chandrasekar, M.; Sundhari, D.; Sivakumar, S.; Raja Saravanan, M.E.; Uthrakumar, R.; Inmozhi, C.
Abstract: BisPicolonium tartrate (BPT) is an organic nonlinear optical crystal has been synthesized and grown by slow evaporation technique. Single crystal X-ray diffraction study reveals that the crystal belongs to triclinic system. Powder X-ray diffraction was recorded and the peaks were indexed. The functional groups present in the crystal were interpreted by FTIR spectral analysis. Optical absorption spectrum shows that the crystal is transparent in the entire visible region. The study of dielectric constant and dielectric loss for the grown crystal were carried out. The relative SHG efficiency of the material was investigated.